Cadmium exposure as a contributing factor to hepato-renal injury in apparently healthy active cigarette smokers in buea-cameroon - Jr Nyambi Nkiackmenyi Ramin; Arnaud Fondjo Kouam; Elisabeth Menkem Zeuko’o; Armel Jackson Seukep; Armelle Gaelle Kwesseu Fepa; Fils Armand Ella; Pascal Dieudonné Chuisseu Djamen; Frédéric Nico Njayou; Paul Fewou Moundipa; Emmanuel Acha Asongalem (PLoS ONE, 2026)
Cigarette smoke contains numerous toxicants, including cadmium, polycyclic aromatic hydrocarbons (PAHs), tobacco-specific nitrosamines (TSNAs), and volatile organic compounds, all of which may contribute to hepato-renal injury. This study, conducted in Buea (Southwest Region, Cameroon), aimed to assess cadmium inhalation exposure from cigarette smoking as a contributing factor to altered liver and kidney function biomarkers in apparently healthy smokers, while acknowledging that combined exposure to multiple co-toxicants may potentiate organ dysfunction. A survey was used to recruit smokers and collect data on their smoking habits. Cadmium contents in the major cigarette brands selected were used to estimate the cadmium Daily Exposure (DE), Weekly Inhalational Exposure (WIE) and the percentage contribution to the Tolerable Weekly Intake (TWI) of cadmium. Serum alanine aminotransferase (ALT) activity, urea, creatinine contents, and urinary albuminuria and glucosuria were measured in blood and urine samples from smokers and nonsmokers. The 102 smokers enrolled were categorized respectively as light (37.3%; 38/102), moderate (38.2%; 39/102), and heavy (24.5%; 25/102) smokers, smoking an average number of 4.7 ± 0.5, 9.1 ± 1.5, and 19.1 ± 3.0 cigarettes/day, respectively. Cadmium levels in cigarette brands ranged from 0.72–1.08 µg Cd per gram of tobacco removed from the cigarette. Heavy smokers exceeded the permitted cadmium No Significant Risk Level (NSRL) by up to 28-fold, contributing 4–8% to the cadmium TWI. Serum ALT activity and creatinine content were significantly higher ( P < 0.05) in smokers groups compared to non-smokers. Also, moderate and heavy smokers were at a significantly higher risk (relative risk 6.90–13.32; P < 0.05) of displaying abnormal elevated serum urea content, positive albuminuria and glucosuria. Our findings demonstrate that healthy active smokers are highly exposed to cadmium (and potentially to other cigarette toxicants) and are at significantly higher risk of displaying abnormally elevated levels of biochemical markers of liver and kidney function, suggesting early signs of organ damage.